Ridge-to-reef conservation avoids future deforestation and sediment exposure of coral reefs - Dominic Muenzel; Eleanor Stewart; Noviar Andayani; Alex J. Dumbrell; Jamaluddin Jompa; Gino Limmon; Jatna Supriatna; Johny S. Tasirin; Nurul L. Winarni; Zuliyanto Zakaria; Zoe G. Davies; Matthew J. Struebig; et al. (Biological Conservation, 2026)

Millennial-scale reef assemblage shifts in the Spermonde Archipelago, Makassar Strait, Indonesia - Michael G. Hynes; Dedi Parenden; Sai Ke; Kiri Spanowicz; Halwi Masdar; Singgih Afifa Putra; Rohani Ambo-Rappe; Jamaluddin Jompa; Jody M. Webster; Bert W. Hoeksema; Nicole J. de Voogd; Willem Renema (Coral Reefs, 2026)
The Coral Triangle is the region in the Indo-Pacific with the highest diversity of reef organisms. Coral reefs here have experienced increased anthropogenic stressors since the late 1970s due to destructive fishing, land reclamation, industrialization, and agriculture. Biological observations in the Spermonde Archipelago (SW Sulawesi, Indonesia) started only after large-scale disturbances had begun limiting insights into long-term reef assemblage dynamics. To address this knowledge gap and mitigate shifting baseline bias, we documented assemblage shifts over centennial/millennial timescales using 16 reef sediment cores from two islands in this area. These cores, previously dated using radiocarbon methods, documented the geomorphic history of these islands. We expand upon this by investigating coral, sponge, and foraminifera assemblage shifts over the past 7200 years. Our findings reveal transitions from more mixed growth forms (foliose, massive, and free-living) to predominantly branching Acroporidae over the last 6000 years, likely driven by changing sea-level regimes. The scleractinian species Palauastrea ramosa (Yabe and Sugiyama 1941) was represented in several core samples but has never been observed in modern surveys, suggesting a historical shift in coral assemblages. Foraminiferal assemblages on the reef flat transitioned from dominance of coral/rubble-associated taxa to more algal-associated substrates in recent times. Sponge spicule assemblages indicate a persistence of cryptic/excavating sponges over the past 2000 years. Since these sponges are associated with coral rubble, their presence suggests that declining coral cover has created more rubble habitat in recent millennia. These findings demonstrate that assemblage shifts began centuries to millennia before modern anthropogenic stressors accelerated these changes.

Coral reef restoration in Indonesia: lessons learnt from the world’s largest coral restoration nation - Rowan Watt-Pringle; Tries B. Razak; Jamaluddin Jompa; Rohani Ambo-Rappe; Alyssa N. Kostaman; David J. Smith (Biodiversity and Conservation, 2024)

Island accretion within a degraded reef ecosystem suggests adaptability to ecological transitions - Yannis Kappelmann; Meghna Sengupta; Thomas Mann; Marleen Stuhr; Dominik Kneer; Jamaluddin Jompa; Hildegard Westphal (Sedimentary Geology, 2024)

Assessing coral reef conservation planning in Wakatobi National Park (Indonesia) from larval connectivity networks - Irfana Diah Faryuni; Antoine Saint-Amand; Thomas Dobbelaere; Widyastuti Umar; Jamaluddin Jompa; Abigail Mary Moore; Emmanuel Hanert (Coral Reefs, 2024)

Reduced small-scale structural complexity on sponge-dominated areas of Indo-Pacific coral reefs - Alberto Rovellini; Charlotte L. Mortimer; Matthew R. Dunn; Elizabeth A. Fulton; Jamaluddin Jompa; Abdul Haris; James J. Bell (Marine Environmental Research, 2024)

The transference of marine protected area management authority in Indonesia: Problems encountered, consequences and ways to move forward - Jamaluddin Jompa; Amanda Pricella Putri; Abigail Mary Moore; Hartati Tamti; Siti Haerani (Marine Policy, 2023)

Transitions from coral to sponge-dominated states alter trophodynamics in associated coral reef fish assemblages - Charlotte L. Mortimer; Sarah Bury; Matthew R. Dunn; Abdul Haris; Jamaluddin Jompa; James J. Bell (Anthropocene, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Suppressed recovery of functionally important branching Acropora drives coral community composition changes following mass bleaching in Indonesia - Rowan Watt-Pringle; David J. Smith; Rohani Ambo-Rappe; Timothy A. C. Lamont; Jamaluddin Jompa (Coral Reefs, 2022)

eDNA metabarcoding of decapod crustaceans across Indonesian seas has implications for biodiversity conservation and fisheries sustainability - Hawis Madduppa; Lalu M. Iqbal Sani; Kuncoro Catur Nugroho; Dietriech G. Bengen; Zainal Abidin Muchlisin; Nur Fadli; Beginer Subhan; Dondy Arafat; Neviaty P. Zamani; Adriani Sunuddin; Meutia Samira Ismet; Endang S. Srimariana; et al. (Frontiers in Marine Science, 2022)
Environmental DNA (eDNA) methods are increasingly viewed as alternate or complementary approaches to conventional capture-based surveys for marine conservation and fisheries management purposes, especially at large spatial scales in mega-biodiversity regions such as Indonesia. Decapod crustacean distribution and diversity across Indonesia are still poorly known, even for economically important fisheries commodities. This study assessed coral reef associated decapod diversity and distribution by sampling 40 sites in three regions (West, Central, East), representing 17 provinces and 10 Fisheries Management Areas (FMAs) across Indonesia, with a special focus on the blue swimming crab Portunus pelagicus . DNA sequencing (Illumina iSeq100) data were analysed in mBRAVE (Multiplex Barcode Research And Visualization Environment) yielded 406 OTUs belonging to 32 families, with 47 genera and 51 species identified. The number of families identified was highest in the Central region (25), while the most genera (31) and species (36) were identified in the West region. Alpha diversity did not differ significantly between regions or provinces, while Beta diversity differed significantly between provinces but not between regions. Our results also showed 31 species are possibility native based on the distribution meanwhile 12 species do not appear to have been recorded based of SeaLifeBase or WorMS. While providing a reference for further exploration of Indonesian coastal and small island decapod biodiversity, the high proportion of unidentified taxa calls for concerted efforts to develop and maintain reference specimen and sequence repositories and expand species conservation status assessments. The economically important decapod crustaceans identified in this study included three crabs ( Charybdis anisodon, Charybdis japonica, Portunus pelagicus ), a freshwater prawn ( Macrobrachium nipponense ), a lobster ( Panulirus stimpsoni ) and two penaeid shrimps ( Mierspenaeopsis hardwickii and Trachysalambria aspera ). For most decapod taxa, observed patterns indicate management under existing provincial and/or FMA level management structures is appropriate. Furthermore, the data can inform science-based fisheries management strategies, in particular for P. pelagicus .

Mitochondrial Cytochrome Oxidase Subunit 1: A Promising Molecular Marker for Species Identification in Foraminifera - Elsa B. Girard; Anouk Langerak; Jamaluddin Jompa; Owen S. Wangensteen; Jan-Niklas Macher; Willem Renema (Frontiers in Marine Science, 2022)
Traditional morphological methods for species identification are highly time consuming, especially for small organisms, such as Foraminifera, a group of shell-building microbial eukaryotes. To analyze large amounts of samples more efficiently, species identification methods have extended to molecular tools in the last few decades. Although a wide range of phyla have good markers available, for Foraminifera only one hypervariable marker from the ribosomal region (18S) is widely used. Recently a new mitochondrial marker cytochrome oxidase subunit 1 (COI) has been sequenced. Here we investigate whether this marker has a higher potential for species identification compared to the ribosomal marker. We explore the genetic variability of both the 18S and COI markers in 22 benthic foraminiferal morphospecies (orders Miliolida and Rotaliida). Using single-cell DNA, the genetic variability within specimens (intra) and between specimens (inter) of each species was assessed using next-generation sequencing. Amplification success rate was twice as high for COI (151/200 specimens) than for 18S (73/200 specimens). The COI marker showed greatly decreased intra- and inter-specimen variability compared to 18S in six out of seven selected species. The 18S phylogenetic reconstruction fails to adequately cluster multiple species together in contrast to COI. Additionally, the COI marker helped recognize misclassified specimens difficult to morphologically identify to the species level. Integrative taxonomy, combining morphological and molecular characteristics, provides a robust picture of the foraminiferal species diversity. Finally, we suggest the use of a set of sequences (two or more) to describe species showing intra-genomic variability additionally to using multiple markers. Our findings highlight the potential of the newly discovered mitochondrial marker for molecular species identification and metabarcoding purposes.

Interactions between coral restoration and fish assemblages: implications for reef management - Marie J. Seraphim; Katherine A. Sloman; Mhairi E. Alexander; Noel Janetski; Jamaluddin Jompa; Rohani Ambo‐Rappe; Donna Snellgrove; Frank Mars; Alastair R. Harborne (Journal of Fish Biology, 2020)
Corals create complex reef structures that provide both habitat and food for many fish species. Because of numerous natural and anthropogenic threats, many coral reefs are currently being degraded, endangering the fish assemblages they support. Coral reef restoration, an active ecological management tool, may help reverse some of the current trends in reef degradation through the transplantation of stony corals. Although restoration techniques have been extensively reviewed in relation to coral survival, our understanding of the effects of adding live coral cover and complexity on fishes is in its infancy with a lack of scientifically validated research. This study reviews the limited data on reef restoration and fish assemblages, and complements this with the more extensive understanding of complex interactions between natural reefs and fishes and how this might inform restoration efforts. It also discusses which key fish species or functional groups may promote, facilitate or inhibit restoration efforts and, in turn, how restoration efforts can be optimised to enhance coral fish assemblages. By highlighting critical knowledge gaps in relation to fishes and restoration interactions, the study aims to stimulate research into the role of reef fishes in restoration projects. A greater understanding of the functional roles of reef fishes would also help inform whether restoration projects can return fish assemblages to their natural compositions or whether alternative species compositions develop, and over what timeframe. Although alleviation of local and global reef stressors remains a priority, reef restoration is an important tool; an increased understanding of the interactions between replanted corals and the fishes they support is critical for ensuring its success for people and nature.

Widespread low abundance despite habitat availability elevates extinction risk in pygmy seahorses - Maarten De Brauwer; Jean-Paul A. Hobbs; Jamaluddin Jompa (Coral Reefs, 2020)
Due to difficulties with surveying, cryptobenthic fishes are understudied, which limits assessments of their extinction risk. Using a novel survey method (a combination of underwater visual census and underwater biofluorescence census), we surveyed the densities of two gorgonian seafan-associated pygmy seahorses ( Hippocampus bargibanti and H. denise ) in 63 sites across Indonesia. Densities were low for both seahorses (≤ 0.4 seahorses/host) and their hosts (≤ 0.25 seafans/200 m 2 ). These low densities, combined with habitat specialisation, increase extinction risk. We failed to detect regional or depth patterns in seahorse abundance per host or group size in occupied hosts. Host occupancy rates were low (< 13.7%), suggesting that other factors than habitat availability constrain pygmy seahorse population size. The low densities found in this study highlight the high extinction vulnerability for habitat specialists on coral reefs.

Management of the Grouper Export Trade in Indonesia - Miftakhul Khasanah; Nadiarti Nurdin; Yvonne Sadovy de Mitcheson; Jamaluddin Jompa (Reviews in Fisheries Science & Aquaculture, 2020)

Unexpected discovery of Diadema clarki in the Coral Triangle - Abigail Mary Moore; Asmi Citra Malina Tassakka; Rohani Ambo-Rappe; Inayah Yasir; David John Smith; Jamaluddin Jompa (Marine Biodiversity, 2019)

Biofluorescence as a survey tool for cryptic marine species - Maarten De Brauwer; Jean‐Paul A. Hobbs; Rohani Ambo‐Rappe; Jamaluddin Jompa; Euan S. Harvey; Jennifer L. McIlwain (Conservation Biology, 2018)
As ecosystems come under increasing anthropogenic pressure, rare species face the highest risk of extinction. Paradoxically, data necessary to evaluate the conservation status of rare species are often lacking because of the challenges of detecting species with low abundance. One group of fishes subject to this undersampling bias are those with cryptic body patterns. Twenty‐one percent of cryptic fish species assessed for their extinction risk (International Union for Conservation of Nature [IUCN]) are data deficient. We developed a nondestructive method for surveying cryptically patterned marine fishes based on the presence of biofluorescence (underwater biofluorescence census, UBC). Blue LED torches were used to investigate how widespread biofluorescence was in cryptic reef fishes in the Coral Triangle region. The effectiveness of UBC to generate abundance data was tested on a data‐deficient pygmy seahorse species ( Hippocampus bargibanti ) and compared with data obtained from standard underwater visual census (UVC) surveys. We recorded 95 reef fish species displaying biofluorescence, 73 of which had not been previously described as biofluorescent. Of those fish with cryptic patterns, 87% were biofluorescent compared with 9% for noncryptic fishes. The probability of species displaying biofluorescence was 70.9 times greater for cryptic species than for noncryptic species. Almost twice the number of H. bargibanti was counted using the UBC compared with UVC. For 2 triplefin species ( Ucla xenogrammus , Enneapterygius tutuilae ), the abundance detected with UBC was triple that detected with UVC. The UBC method was effective at finding cryptic species that would otherwise be difficult to detect and thus will reduce interobserver variability inherent to UVC surveys. Biofluorescence is ubiquitous in cryptic fishes, making this method applicable across a wide range of species. Data collected using UBC could be used with multiple IUCN criteria to assess the extinction risk of cryptic species. Adopting this technique will enhance researchers’ ability to survey cryptic species and facilitate management and conservation of cryptic marine species.

Contrasting Responses in the Niches of Two Coral Reef Herbivores Along a Gradient of Habitat Disturbance in the Spermonde Archipelago, Indonesia - Jeremiah G. Plass-Johnson; Vanessa N. Bednarz; Jaclyn M. Hill; Jamaluddin Jompa; Sebastian C. A. Ferse; Mirta Teichberg (Frontiers in Marine Science, 2018)

Evaluating the core microbiota in complex communities: A systematic investigation - Carmen Astudillo‐García; James J. Bell; Nicole S. Webster; Bettina Glasl; Jamaluddin Jompa; Jose M. Montoya; Michael W. Taylor (Environmental Microbiology, 2017)
Summary The study of complex microbial communities poses unique conceptual and analytical challenges, with microbial species potentially numbering in the thousands. With transient or allochthonous microorganisms often adding to this complexity, a ‘core’ microbiota approach, focusing only on the stable and permanent members of the community, is becoming increasingly popular. Given the various ways of defining a core microbiota, it is prudent to examine whether the definition of the core impacts upon the results obtained. Here we used complex marine sponge microbiotas and undertook a systematic evaluation of the degree to which different factors used to define the core influenced the conclusions. Significant differences in alpha‐ and beta‐diversity were detected using some but not all core definitions. However, findings related to host specificity and environmental quality were largely insensitive to major changes in the core microbiota definition. Furthermore, none of the applied definitions altered our perception of the ecological networks summarising interactions among bacteria within the sponges. These results suggest that, while care should still be taken in interpretation, the core microbiota approach is surprisingly robust, at least for comparing microbiotas of closely related samples.

Mangrove and Seagrass Beds Provide Different Biogeochemical Services for Corals Threatened by Climate Change - Emma F. Camp; David J. Suggett; Gilberte Gendron; Jamaluddin Jompa; Carrie Manfrino; David J. Smith (Frontiers in Marine Science, 2016)

High levels of heterospecific cohabitation among anemonefishes in Hoga Island, Indonesia - Maarten De Brauwer; Emma Camp; Jamaluddin Jompa; David J. Smith (Marine Biodiversity, 2016)

A recent outbreak of crown-of-thorns starfish (Acanthaster planci) in the Spermonde Archipelago, Indonesia - Jeremiah G. Plass-Johnson; Hauke Schwieder; Jasmin Heiden; Laura Weiand; Christian Wild; Jamaluddin Jompa; Sebastian C. A. Ferse; Mirta Teichberg (Regional Environmental Change, 2015)

Fish herbivory as key ecological function in a heavily degraded coral reef system - Jeremiah G. Plass‐Johnson; Sebastian C. A. Ferse; Jamaluddin Jompa; Christian Wild; Mirta Teichberg (Limnology and Oceanography, 2015)
Localized impacts, such as eutrophication and overfishing, have been identified as major threats to reefs worldwide, resulting in changes in coral reef community composition, from coral‐dominance to algal‐dominance. Herbivory by fishes is frequently cited as a key process structuring benthic community response to stressors. Here, we experimentally tested the capacity of herbivorous fishes to remove macroalgae along an onshore–offshore spatial gradient in the Spermonde Archipelago, Indonesia; a coral reef system exposed to long‐term anthropogenic disturbances. Bioassays of Sargassum and Padina spp. were collected from the reef flat and transplanted onto the reef slope at five islands varying in distance (1–55 km) from the coastline and city of Makassar, South Sulawesi. Supplementary underwater video deployment and fish surveys were used to identify species‐specific differences in herbivore communities and rates of algal removal. Over a 24 h period, Padina was almost completely removed from the two outermost islands, but removal declined toward shore. With the exception of the site closest to Makassar, more than 50% of all transplanted macroalgae were removed. Species diversity of algal‐consuming fishes and total bites increased toward off‐shore, with only one species, Siganus virgatus (Siganidae), feeding at all sites. These changes in herbivore communities underline the capacity for functional resilience under varying levels of reef degradation. Our results exemplify the complexities of ecological functioning along environmental gradients.

The effects of nutrients and herbivory on competition between a hard coral ( Poritescylindrica ) and a brown alga ( Lobophora variegata ) - Jamaluddin Jompa; Laurence J. McCook (Limnology and Oceanography, 2002)
Coral reef degradation often involves a phase shift from coral‐ to macroalgal‐dominated reefs. Declining levels of herbivory or increasing supply of nutrients have both been suggested as a cause of increased algal abundance and consequent competitive overgrowth of corals. However, explicit demonstration of the processes involved and their relative strengths requires simultaneous tests of all three factors: competition, herbivory, and nutrient effects. We experimentally tested the factorial effects of nutrients and herbivory on the competitive interaction between a brown alga Lobophora variegata and a scleractinian coral Porites cylindrica . The results of the experiment show that coral tissue mortality was strongly enhanced by the presence of the competitor ( L. variegata ), and this effect was significantly greater when herbivores were excluded. In contrast, the coral growth (skeletal extension) of P. cylindrica was not significantly affected by any treatments. The addition of nutrients did not have a significant effect on corals overall, but had a small effect on algal growth and consequent coral tissue mortality when herbivores were excluded. The factorial combination of treatments in this experiment allows interpretation of the causal relationships between each factor, demonstrating that nutrient effects on algal growth only led to competitive effects on corals when herbivory was insufficient to consume excess algal growth and that both herbivore and nutrient effects on corals were dependent on the strength and outcome of the competitive interaction between corals and algae.